Anselm Kiefer - field of the cloth of gold - Kiefer, Anselm 1945-; Calvocoressi, Richard 1951- (Gagosian, 2021)
This book was published on the occasion of the exhibition Anselm Kiefer: Field of the Cloth of Gold at Gagosian, Le Bourget. It features six monumental paintings completed between 2019 and 2020, as well as recent large-scale paintings and artist's books. The layered and visceral character of these compositions, whose scale almost matches the landscapes they depict, evokes the surging capriciousness of European history and the effects and aftermaths of war. As is customary in Kiefer's work, each painting's title and symbols contain a rich set of literary and historical references. Alongside reproductions of the exhibited works and installation photography, the bilingual (English/French) publication includes a new text by Richard Calvocoressi. Exhibition: Gagosian, Le Bourget, France (07.02.-26.06.2021)
Impressum: Published on the occasion of the exhibition "Anselm Kiefer. Field of Cloth of Gold", February 7-June 26, 2021, Gagosian, Le Bourget
Keywords: Kiefer, Anselm -- 1945-; Kiefer, Anselm / 1945- / Exhibitions; Calvocoressi, Richard / contributor; Calvocoressi, Richard; Kiefer, Anselm / 1945-; Exhibition catalogs; Ausstellungskatalog -- Gagosian Gallery -- 07.02.2021-26.06.2021 -- Le Bourget